Aluminium-induced changes of fusion pore properties attenuate prolactin secretion in rat pituitary lactotrophs - Calejo, A. I. (2019)
Hormone secretion is mediated by Ca(2+)-regulated exocytosis. The key step of this process consists of the merger of the vesicle and the plasma membranes, leading to the formation of a fusion pore. This is an aqueous channel through which molecules stored in the vesicle lumen exit into the extracellular space on stimulation. Here we studied the effect of sub-lethal dose of aluminium on prolactin secretion in isolated rat pituitary lactotrophs with an enzyme immunoassay and by monitoring electrophysiologically the interaction of a single vesicle with the plasma membrane in real time, by monitoring membrane capacitance. After 24-h exposure to sub-lethal AlCl(3) (30 μM), the secretion of prolactin was reduced by 14±8% and 46±11% under spontaneous and K(+)-stimulated conditions, respectively. The frequency of unitary exocytotic events, recorded by the high-resolution patch-clamp monitoring of membrane capacitance, a parameter linearly related to the membrane area, under spontaneous and stimulated conditions, was decreased in aluminium-treated cells. Moreover, while the fusion pore dwell-time was increased in the presence of aluminium, the fusion pore conductance, a measure of fusion pore diameter, was reduced, both under spontaneous and stimulated conditions. These results suggest that sub-lethal aluminium concentrations reduce prolactin secretion downstream of the stimulus secretion coupling by decreasing the frequency of unitary exocytotic events and by stabilizing the fusion pore diameter to a value smaller than prolactin molecule, thus preventing its discharge into the extracellular space.